(3cfR GdahGFO aj JfhjY GdehGFOs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3eHJhQ GdChd hChd GdehLhO efg(B: (3HGdQWd GdYQGbi hgh eGFI hKdGKhf OQgekG, hjdbi Ydjg eGFI hNeShf OQgekG ScQkG hYSd fMd aEPG EfMd GdScQ hjMQc MJi jNJdW Ke ojUHZ GdRYaQGf hojQT Ydi QCS GdbOQ s
(3BNQgG (B:s
(3hEPG CQOJ EONGQ GdYfH Ydi GdcQe EPG ESJhi jNQL efg YfH ai ZjQ GhGfg fLR cJGH cfR GdahGFO aj JfhjY GdehGFO hGdMeO ddg QH GdYGdejf s
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B386 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGHG dKGfj (B- (3U (B210 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs